A new alkanol from the endolichenic fungus Daldinia childiae. Issue 4 (20th November 2020) - Zhou, Xuan; Yang, Cailing; Meng, Qingfeng; Liu, Le; Fu, Shaobin
Abstract: One new alkanol, 2, 4, 5‐heptanetriol(1 ), together with four compounds, 6‐heptene‐2, 4, 5‐triol (2 ), rel‐(1 S, 4 S, 5 R, 7 R, 10 R )‐10‐desmethyl‐1‐methyl‐11‐eudesmene (3 ), 2, 3‐dihydro‐5‐hydroxy‐2‐methyl‐4 H ‐1‐benzopyran‐4‐one (4 ), (−)‐regiolone (5 ) were isolated from the ethyl acetate extract of rice solid‐substrate cultures of endolichenic fungus Daldinia childiae for the first time. Compounds 1, 2, and 3 were separated firstly from the genus Daldinia . Their structures were elucidated by spectral data and compound 3 exhibited α‐amylase inhibitory activity. Abstract : One new alkanol, 2, 4, 5‐heptanetriol(1 ), together with four compounds, 6‐heptene‐2, 4, 5‐triol (2 ), rel‐(1 S, 4 S, 5 R, 7 R, 10 R )‐10‐desmethyl‐1‐methyl‐11‐eudesmene (3 ), 2, 3‐dihydro‐5‐hydroxy‐2‐methyl‐4 H ‐1‐benzopyran‐4‐one (4 ), (−)‐regiolone (5 ) were isolated from the ethyl acetate extract of rice solid‐substrate cultures of endolichenic fungus Daldinia childiae for the first time. Compounds 1, 2, and 3 were separated firstly from the genus Daldinia . Their structures were elucidated by spectral data and compound 3 exhibited α‐amylase inhibitory activity.